PLO User Interface based on Telegram Bot - Bambang Nurcahyo Prastowo; Nur Achmad Sulistyo Putro; Oktaf Agni Dhewa (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2019)
Instant messaging services usually integrate a notification system on their users’ devices, as phone calls and short message service (SMS) systems do. Telegram is – as far as we are aware – the only popular instant messaging service that uses open source code. Telegram also provides APIs for their users, enabling the development of a bot system that allows instant messaging application to access information. Here, we study the potential use of Telegram bot as a user interface to a paperless office (PLO) system developed in our institution. We found that Telegram bot improves communication among the users; however, as the amount of messages increased, the server becomes overloaded. This limitation suggests that future works need to be directed to improving the efficiency of the bot